Optical spectroscopic analysis, supercapacitance, photocatalysis of BaTixFe12-(4/3)xO19 hexagonal nanoparticles - Amina Ibrahim Ghoneim (Open Journal of Chemistry - Peertechz Publications, 2023)
Obviously, BaTixFe12-(4/3)xO19 Hexagonal nanocrystals are excellent candidates as photocatalysts in water purification, as well as using them as electrode materials for supercapacitors and energy storage applications. M-Type Hexagonal nanoparticles (BaTixFe12-(4/3)xO19, 0 ≤ x ≤ 1) with the magneto-plumbite structure were formerly synthesized by co-precipitation procedure and investigated by several techniques such as XRD, FT-IR, Raman, Photoluminescence and UV-VL. XRD and FT-IR confirmed the structure, and Raman spectra showed 12 characterizing summits. Photoluminescence emission spectra indicated two summits at 448 and 501 nm. Optical UV-VL spectroscopic analysis parameters showed dependence on λ and x. Obviously, BaTi0.75Fe11O19 nanocrystals as a sort of M-Type Hexagonal Ferrites showed excellent Photocatalytic activity on the Degradation of Organic Dyes like; Crystal Violet, Methyl Orange, ... etc. Furthermore; these nanocrystals possess excellent electrochemical performance; which in turn introduces these materials for Supercapacitors Applications. Thus, the Photo-catalytic activity of BaTi0.75Fe11O19 nanocrystals for the decolorization of Crystal Violet (CV) dye (1 × 10-5 M) illuminated excellent photocatalytic efficiency reaching ≈ 85%. On the other hand; BaTi0.75Fe11O19 nanoparticles exhibited a specific capacitance of 1858 mF/g at 50 mV/s. The current study introduces promising applications of BaTi0.75Fe11O19 nanoparticles as electrode materials for super capacitance and energy storage.